(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the process of multi-year sports training of young female athletes subject to the general laws of education and upbringing, and general pedagogical principles are naturally reflected in this. The general principles of sports training also apply to the training of the sports reserve: in-depth specialization and individualization, the unity of general and special training, gradualism, the cyclical nature of the training process, and others. At the same time, these principles applied to young female athletes have their own characteristics, which are determined by the peculiarities of the age-related development of children and adolescents. The purpose of the study is to develop a model of the age development of athletes with many years of training in field hockey. The goal of the study was realized in the process of solving the following tasks: analysis of scientific and methodical literature and working documentation of coaches, programs of the Field Hockey Academy of Youth and Sports, and the analysis of morpho-functional indicators. Research methods: theoretical analysis of literary sources and generalization of the experience of advanced sports and pedagogical practice; analysis of documentary materials; pedagogical observation. Considering the research problem, models of long-term training of female athletes were analyzed, which are used in the strategy, normalization of training and competitive loads at separate stages of training, it is necessary to take into account the age-related patterns of development of individual functional systems and the body as a whole, such as: heterochrony of development, sensitive periods, development of physical qualities , the influence of individual rates of biological maturation, and the dynamics of the development of basic qualities and sports achievements. The generalized results are presented in the form of tables.